Aplicação do Knowledge Management System na análise de falhas em uma empresa do setor elétrico - Almeida, Dagoberto Alves de; Fagundes, Liliane Dolores (Revista Gestão da Produção Operações e Sistemas, 2006)
The companies’ ability to produce, store, disseminate and use knowledge is more and more related to the successof the organization. This importance is intensified when the knowledge is used in order to analyze the faults,with the purpose of preventing from the occurrence of problems and increasing the systems’ trustability. Withinthis context, this paper presents the application of the Knowledge Management System for the fault analysis inan electric company by means of the mapping, that is, by means of the fault map development which illustratesthe architecture of the formation process of the faults in the companies. The intention is that these maps becomeuseful tools for the management of the faults in the mentioned company, once their investigation will help toprevent their reoccurrence, or in case they reoccur, details will be provided so that a fast solution can be applied.In order to build such fault maps, the Knowledge Management System and an information system model wereused facilitating the obtainment of the information.Keywords: Knowledge management; Information systems; Fault analysis.